Some Penta-Coordinated Complexes of Oxovanadium(IV) with 4[N-(3,4,5-Trimethoxy Benzylidene) Amino] Antipyrine - Garg, Priyanka; Chakraborthi, Indranil; K. Manglik, Ajay (Asian Journal of Chemistry, 2012)
In the present note, a series of penta-coordinated complexes of VO2+ with 4[N-(3,4,5-trimethoxy benzylidene) amino] antipyrine (TMBAAP) with the general composition VOX2.n(TMBAAP) (X = Cl–, Br–, I–, NO3–, or NCS, n = 1; X = ClO4–, n = 2) have been synthesized and characterized. The IR data reveal the bidentate nature (N,O) of the ligand. The probable coordination number of the central metal ion is found to be five. Thermal stabilities of the complexes have been studied through thermogravimetric analysis.